2022
DOI: 10.1097/brs.0000000000004413
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Gender-based Global Sagittal Spinal Alignment in Asymptomatic Adult Volunteers: Results of the Multiethnic Alignment Normative Study (MEANS)

Abstract: Study Design. Multicenter Cohort. Objective. Assess normative values of sagittal spinal and lower extremity alignment in asymptomatic volunteers stratified by age and gender. Summary of Background Data. Our understanding of ideal sagittal alignment is still evolving. The Multiethnic Alignment Normative Study (MEANS) investigated skeletal alignment of the largest multiethnic cohort of asymptomatic adult volunteers. We aim to assess normative values of sagittal spinal and lower extremity alignment in asymptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Roussouly et al 2 further expanded this concept to describe variations in normative alignment based on the reciprocal relationship between each individual's pelvic incidence, sacral slope, and pelvic tilt while more recently the Multiethnic Alignment Normative Study demonstrated that thoracic kyphosis progresses slowly with age, whereas lumbar lordosis remains stable in asymptomatic patients. 9 Additional studies have demonstrated that deformity and spinal malalignment are directly associated with quality-of-life outcomes and failure to address these parameters may increase the risk of mechanical complications after spine surgery. 10 Given the importance of these measurements on long-term outcomes, the rationale for tailoring treatment based on each individual's alignment goals becomes evident.…”
Section: Background and Overviewmentioning
confidence: 99%
“…Roussouly et al 2 further expanded this concept to describe variations in normative alignment based on the reciprocal relationship between each individual's pelvic incidence, sacral slope, and pelvic tilt while more recently the Multiethnic Alignment Normative Study demonstrated that thoracic kyphosis progresses slowly with age, whereas lumbar lordosis remains stable in asymptomatic patients. 9 Additional studies have demonstrated that deformity and spinal malalignment are directly associated with quality-of-life outcomes and failure to address these parameters may increase the risk of mechanical complications after spine surgery. 10 Given the importance of these measurements on long-term outcomes, the rationale for tailoring treatment based on each individual's alignment goals becomes evident.…”
Section: Background and Overviewmentioning
confidence: 99%